2016
DOI: 10.1002/jat.3426
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-rich diet aggravates monocrotophos-induced dopaminergic neuronal dysfunction inCaenorhabditis elegans

Abstract: The present study aimed to obtain insights into the mechanism(s) by which glucose-rich diet aggravates monocrotophos (MCP)-induced dopaminergic neuronal dysfunction in Caenorhabditis elegans. In this study, we exposed three different strains of worms (wild-type N2, CB1112 (cat-2(e1112)II, tyrosine hydroxylase-deficient mutant, catecholamine absent) and the transgenic BZ555 (egls1-dat-1p::green fluorescent protein [GFP]) (in which bright GFP is tagged to the dopamine neuronal soma and processes) grown and maint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 63 publications
1
10
3
Order By: Relevance
“…Recent studies in mice found that a high-glucose diet significantly impaired healing following a tendon injury (65,66), demonstrating that high-sugar diets have far-reaching effects. Similar to previous studies (5)(6)(7)(8)(10)(11)(12)(13) and data in Fig. 1, we found that addition of glucose to the C. elegans diet leads to shortened lifespan, diminished healthy aging or healthspan, and increased AGEs.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Recent studies in mice found that a high-glucose diet significantly impaired healing following a tendon injury (65,66), demonstrating that high-sugar diets have far-reaching effects. Similar to previous studies (5)(6)(7)(8)(10)(11)(12)(13) and data in Fig. 1, we found that addition of glucose to the C. elegans diet leads to shortened lifespan, diminished healthy aging or healthspan, and increased AGEs.…”
Section: Discussionsupporting
confidence: 91%
“…According to the US Department of Agriculture, the average individual consumed almost 100 pounds of sugar in 2015, more than double the amount consumed in 1900 (4). The effects of a high-sugar diet can be modeled in Caenorhabditis elegans, as the addition of glucose to the standard Escherichia coli diet has been shown to cause glucose toxicity, which results in a decrease in lifespan (5)(6)(7)(8), an increase in triglycerides (7,8), neuronal defects (9,10), and a decrease in locomotion (11,12). Intracellularly, excess glucose can also lead to a greater incidence of advanced glycation end products (AGEs) in both humans and C. elegans (13).…”
mentioning
confidence: 99%
“…Therefore, worm’s dopaminergic behaviors including BSR and alcohol avoidance are more deteriorated by high-glucose-diet-induced specific and early degeneration of ADE neurons. More deterioration of ADE than CEP was also found in the previous study focusing on a synergetic effect of a glucose-rich diet on insecticide-induced dopaminergic neuronal dysfunction in C. elegans.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, worm's dopaminergic behaviors including BSR and alcohol avoidance are more deteriorated by highglucose-diet-induced specific and early degeneration of ADE neurons. More deterioration of ADE than CEP was also found in the previous study 59 focusing on a synergetic effect of a glucose-rich diet on insecticide-induced dopaminergic neuronal dysfunction in C. elegans. Without insecticides, we here found that a high-glucose diet independently induced dopaminergic neuronal dysfunction in C. elegans through the reduction of dopamine synthesis and transport.…”
Section: Discussionmentioning
confidence: 99%
“…Possessing 8 dopaminergic neurons and high genetic tractability, several transgenics have been generated to assist with visualization of dopamine neuron morphology (21, 22). High glucose exposure studies in C. elegans showed increased susceptibility to organophosphate pesticide-induced neurodegeneration in dopaminergic, GABAergic, and cholinergic neurons (17, 18, 23). These studies, however, were mostly performed with acute, developmental exposures to glucose.…”
Section: Introductionmentioning
confidence: 99%